2020
DOI: 10.1101/2020.03.28.013276
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Site-specific N-glycosylation Characterization of Recombinant SARS-CoV-2 Spike Proteins

Abstract: SummaryThe glycoprotein spike (S) on the surface of SARS-CoV-2 is a determinant for viral invasion and host immune response. Herein, we characterized the site-specific N-glycosylation of S protein at the level of intact glycopeptides. All 22 potential N-glycosites were identified in the S-protein protomer and were found to be preserved among the 753 SARS-CoV-2 genome sequences. The glycosites exhibited glycoform heterogeneity as expected for a human cell-expressed protein subun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
99
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(103 citation statements)
references
References 52 publications
2
99
2
Order By: Relevance
“…Two very recent preprints reporting N-glycosylation on spike protein of SARS-CoV-2 showed different glycosylation profiles, and both reports were different from our results although all three studies utilized recombinant S protein from an HEK 293-based expression system (Watanabe, Y., Allen, J.D., et al , Zhang, Y., Zhao, W., et al 2020. This indicates the caution to be exercised in determining the glycosylation on viral antigens generated from various sources as the changes in glycosylation pattern can influence the efficacy of potential vaccine candidates (Chang, D. and Zaia, J.…”
Section: Discussioncontrasting
confidence: 99%
“…Two very recent preprints reporting N-glycosylation on spike protein of SARS-CoV-2 showed different glycosylation profiles, and both reports were different from our results although all three studies utilized recombinant S protein from an HEK 293-based expression system (Watanabe, Y., Allen, J.D., et al , Zhang, Y., Zhao, W., et al 2020. This indicates the caution to be exercised in determining the glycosylation on viral antigens generated from various sources as the changes in glycosylation pattern can influence the efficacy of potential vaccine candidates (Chang, D. and Zaia, J.…”
Section: Discussioncontrasting
confidence: 99%
“…Two very recent preprints reporting N-glycosylation on spike protein of SARS-CoV-2 showed different glycosylation profiles, and both reports were different from our results although all three studies utilized recombinant S protein from an HEK 293-based expression system (Watanabe et al 2020;Zhang et al 2020). Although Watanabe et al (2020) used the entire S protein extracellular domain for the glycoproteomics evaluation, we employed separate recombinant protein subunits S1 and S2 of the spike protein.…”
Section: Discussioncontrasting
confidence: 82%
“…Further experiments are being performed with bile acids and bile salts that act as detergents in gut. Recent studies showed a heavy glycosylation of SARS-CoV-2 S protein (48), and it is possible that the glycan coating confers some stability against the enzymatic digestion and bile salt solubilization. Two recent publications demonstrated that SARS-CoV-2 has unique stability in the laboratory environment (49,50).…”
Section: Discussionmentioning
confidence: 99%